Adherence to the Eat-Lancet Diet and Risk of Stroke and Stroke Subtypes – A Danish Cohort Study. (7th June 2021) - Ibsen, Daniel; Christiansen, Anne; Olsen, Anja; Tjønneland, Anne; Overvad, Kim; Wolk, Alicja; Mortensen, Janne; Dahm, Christina
Abstract: Objectives: To investigate the association between adherence to the EAT-Lancet diet, a sustainable and mostly plant-based diet, and risk of stroke and subtypes of stroke in a Danish population. To explore dietary guidelines that do not take the environmental impact into account, we investigated associations for adherence to the Alternate Healthy Eating Index-2010 (AHEI). Methods: We used the Danish Diet, Cancer and Health cohort ( n = 55, 016) including men and women aged 50–64 years at baseline (1993–1997). A validated food frequency questionnaire was used to assess dietary intake. The EAT-Lancet diet score was the sum of adherence to 14 components (1 point = yes, 0 = no; score ranged 0–14). The AHEI included 11 components and scored relative adherence 0–10 point for each component (score ranged 0–110). Stroke cases were identified using the Danish National Patient Registry and subsequently validated by review of medical records ( n = 2253, median follow-up time = 15 years). Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for associations with the EAT-Lancet diet or the AHEI and risk of stroke and subtypes of stroke (ischemic stroke [IS, n = 1858], intracerebral hemorrhage [ICH, n = 267] and subarachnoid hemorrhage [SAH, n = 115]). Results: In multivariable adjusted models, we found that adherence to the EAT-Lancet diet score was associated with a lower risk of stroke, although not statistically significant, comparing the highest level of adherence (11–14 points) with the lowest (0–7 points) (HR 0.91; 95% CI 0.76, 1.09). A lower risk was observed for the AHEI (highest [59–110 points] vs lowest adherence [0–40] 0.75; 0.64, 0.87). For stroke subtypes we found that adherence to the EAT-Lancet diet was associated with a lower risk of SAH (0.30; 0.12, 0.73) but not IS or ICH. In contrast, the AHEI was associated with a lower risk of IS (0.76; 0.64, 0.90) and ICH (0.58; 0.36, 0.93) but not SAH. Conclusions: Adherence to the EAT-Lancet diet or the AHEI was associated with a lower risk of stroke in a Danish population. The EAT-Lancet diet was mainly associated with a lower risk of SAH, whereas the AHEI was mainly associated with a lower risk of IS and ICH. Funding Sources: Aarhus University, Danish Cancer Society.